A lei Robin Hood e o desenvolvimento dos municípios do Vale do Jequitinhonha - Cruz, Eduardo Cabral da (2016)
In the several countries that the federative system practice itself it is nature the occurrence of transference of assets among the governments´levels (central to sub-national) , that they are considered as primordial for partial payment of public service quality , besides to level out tax-based between ones. Brazil is holder of this political system and present , in state ambit, the state VAT as the main tribute that distribution to cities it is performed about in the FAV each city (75%) and other part (25%) as legislation each state, according to 1988 Federal Constitution .In this case Minas Gerais, distributional criterion were defined by Robin Hood`s law, that bring forward as object to reduce social and economic differences among minas city. The state is divided in 12 subdivision and the Jequitinhonha Valley it highlight itself as the poorest in its place. Due , it mains to examine if the Robin Hood´s law led about development of the municipalities of that region, it is causing the mitigating effect of social and economic differences to aim, it is checking through multiple linear regressions the influence of criterions of the law in indicators :GDP, SRMI, IRFS AND HDI-C. The sample was formed by 51 cities that compound the subdivision Minas city. The temporal scrap was defined by understood period between 2002 to 2003 years. It achieved the descriptive analyse of datas, the correlation of Sperman (out of normality) , the analyse of multicollinearity among the informative variables through of VIF and the backward method for choose the significant independent variables for regressions. The results showed that the development of the municipalities of the Jequitinhonha Valley occurred in a very small way, since even though the acceptance of three of the four statistical hypotheses was accepted, the number of distributive criteria (explanatory variables) May denote legal inefficiency or even municipal management.